Algebraische Zahlentheorie: 10.8. bis 16.8.1975 - Hasse, Helmut; Roquette, Peter (Tagungsbericht, 1975)
S. Agou, Lyon; E. Becker, Köln; H. Benz, Köln; H. Brückner, Hamburg; D. G. Cantor, Los Angeles; H. Cohn, New York; R. W. D. Davis, San Diego; P. Draxl, Bielefeld; M. Eichler, Basel; G. Frei-Imfeld, Zürich; G. Frey, Erlangen; M. D. Fried, Irvine; A. Fröhlich, London; W. D. Geyer, Erlangen; F. Halter-Koch, Essen; H. Hasse, Hamburg; M. Hazewinkel, Rotterdam; H. Jacobinski, Göteborg; M. Jarden, Tel Aviv; W. Jehne, Köln; K. Kiyek, Paderborn; N. Klingen, Köln; M. Kneser, Göttingen; K. Lakkis, Thessaloniki; E. Lamprecht, Saarbrücken; H. Lang, Münster; F. Lorenz, Münster; M. L. Madan, Columbus; G. Martens, Erlangen; C. Meyer, Köln; J. Neukirch, Regensburg; Ch. J. Parry, Blacksburg; J. J. Payan, St. Martin d'Heres; R. Perlis, Regensburg; M. Peters, Münster; G. Poitou, Orsay; G. Prichett, Clinton; P. Ribenboim, Kingston; J. Ritter, Heidelberg; P. Roquette, Heidelberg; W. Scharlau, Münster; R. Schertz, Köln; A. Schinzel, Warschau; V. Schulze, Clausthal-Zellerfeld; H.-J. Stender, Köln; R. J. Stroeker, Rotterdam; H. Stützer, Köln; R. W. van der Waall, Nymwegen; C. Walter, Cambridge; H. G. Zimmer, Saarbrücken; P. Rehm, Karlsruhe